Nota sobre efeitos da aplicação de adubo nitrogenado e fosfatado, calcário e inoculante na cultura do feijão (Phaseolus vulgaris L) - A N Fontes , Luiz (Revista Ceres, 2025)
This paper presents the results of an exploratory study with nitrogen, phosphorus, lime and inoculant on drybean crop carried out in Viçosa, State of Minas Gerais.